2006
DOI: 10.1021/jp064389+
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Vibrational Autodetachment Spectroscopy of Microsolvated Benzonitrile Radical Anions

Abstract: Vibrational spectra of microsolvated benzonitrile radical anions (C6H5CN- -S; S = H2O and CH3OH) were measured by probing the electron detachment efficiency in the 3 microm region, representing resonance bands of autodetachment via OH stretching vibrations of the solvent molecules. The hydrogen-bonded OH band for both the cluster anions exhibited a large shift to the lower energy side with approximately 300 cm-1 compared to those for the corresponding neutral clusters. The solvent molecules are bound collinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Interestingly, the previous gas-phase studies reported a cyclic structure, where the water acts as a single donor and single acceptor through the simultaneous formation of O–D···π and C–H···O H-bonds . In the anionic benzonitrile–water cluster, the single donor-type water ligand linearly binds to the negatively charged benzonitrile moiety via the N···H–O H-bond, which is qualitatively similar to the linear isomer obtained in the helium droplets . However, due to an increased negative charge density on the nitrogen atom, the observed H-bonded red-shift is comparatively higher than the neutral cluster (Δν 1 = 280 cm –1 for H 2 O vs 37 cm –1 for D 2 O).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, the previous gas-phase studies reported a cyclic structure, where the water acts as a single donor and single acceptor through the simultaneous formation of O–D···π and C–H···O H-bonds . In the anionic benzonitrile–water cluster, the single donor-type water ligand linearly binds to the negatively charged benzonitrile moiety via the N···H–O H-bond, which is qualitatively similar to the linear isomer obtained in the helium droplets . However, due to an increased negative charge density on the nitrogen atom, the observed H-bonded red-shift is comparatively higher than the neutral cluster (Δν 1 = 280 cm –1 for H 2 O vs 37 cm –1 for D 2 O).…”
Section: Resultssupporting
confidence: 52%
“…The extraterrestrial detection of benzonitrile has fostered several laboratory studies. A recent study reported the aromatic CH stretching frequencies of cationic benzonitrile (benzonitrile + ) and the formation of a CH···O-type hydrogen bond (H-bond) with polar water solvents . The same group also reported an exclusive nitrogen protonation of this aromatic moiety and a hydration-induced solute-to-solvent proton transfer that causes switching of the H-bond framework from NH···O to N···HO following the addition of two or more water ligands. , While in the anionic benzonitrile–water complex, the solvent water only forms a nearly linear N···HO H-bond with the negatively charged ring, in case of the neutral benzonitrile–water complex based on gas-phase IR and microwave studies of a cyclic global minimum structure, where the solvent water simultaneously forms a OH···π H-bond with π electrons of the CN group and a CH···O H-bond with the adjacent ortho CH proton donor was proposed. Further addition of water molecules leads to the formation of a H-bonded solvent network that results in the expansion of the cyclic water ring present in the monohydrate. Surprisingly, a recent matrix isolation study showed the presence of a linear local minimum structure featuring a N···H–O H-bond .…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational autodetachment spectroscopy can be a powerful technique to obtain infrared spectra of anions and probe the non-adiabatic intramolecular dynamics between the vibrating neutral core and the outgoing electron. [1][2][3][4][5][6] However, it cannot be generally applicable because the probed vibrational levels of the anion must be above the electron detachment threshold for autodetachment to occur. Only a limited set of weakly bound anions have been reported with low enough electron binding energies to realize vibrational autodetachment within the ground electronic state.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited set of weakly bound anions have been reported with low enough electron binding energies to realize vibrational autodetachment within the ground electronic state. [1][2][3][4][5][6][7][8] Valence excited electronic states of anions are also not usually accessible. [9][10][11][12][13][14][15][16] However, the existence of dipole-bound states (DBSs) near the detachment threshold of anions significantly expands the scope of vibrational autodetachment spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Lots of (experimental, theoretical, and computational) research works have shown interest in benzonitrile and its derivatives, and recently, it has found other applications such as cosolvent because of large dipole moment (4.01 D 12 and 4.18 D 13 ) and widespread strong miscibility. [14][15][16] Because of the three different binding sites, benzonitrile has shown interesting adsorption features on metal and non-metal surfaces. So far, various studies have been performed on the adsorption of benzonitrile on the Ag, Ni, Pd, Pt, Au and, Fe-doped carbon nanostructures surfaces.…”
Section: Introductionmentioning
confidence: 99%